(untitled) (American Journal of Life Science and Innovation, 2025)
It is relevant to analyze the concentrations of heavy metals in C. iredalei. This study was conducted to analyze the concentrations of the heavy metal contents, such as copper (Cu), lead (Pb), and zinc (Zn) in C. iredalei from Dumangas and Barotac Nuevo, Iloilo, Philippines. The samples of C. iredalei were analyzed using flame atomic spectrophotometry, and results were compared to regulatory limits set by the International Shellfish Safety and Sanitation Standards. In the town of Dumangas, Pb (mean = 0.01mg/L; sd = 0.11;) Cu (10.44 mg/L; sd = 2.95); and Zn (mean = 3.35 mg/L; sd = 0.13) were within the accepted values set by the regulatory limits of the International Shellfish Safety and Sanitation Standard. The samples of C. iredalei were taken from March 31st and April 7th, 2023. On the other hand, in the town of Barotac Nuevo, Pb (mean = -0.09, mg/L s = 0.02); Cu (mean = 10.14 mg/L, sd = 0.95; and Zn (mean = 3.21 mg/L; sd = 0.10) were within were within the accepted values set by the regulatory limits of the International Shellfish Safety and Sanitation Standard, too. This implies that the C. iredalei samples from farms in towns Dumangas and Barotac, Iloilo, Philippines, were safe for consumption and do not pose threats concerning heavy metal intoxication.